2017
DOI: 10.1111/ijag.12288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chloride ions in Tris buffer solution on bioactive glass apatite mineralization

Abstract: Degradation and apatite precipitation of Bioglass 45S5 were characterized in two different tris(hydroxymethyl)aminomethane (Tris) buffer solutions. In the conventional one, pH was adjusted to 7.4 using hydrochloric acid (Tris-HCl buffer). In the other one, acetic acid was used instead, thereby obtaining a Tris buffer solution, which was virtually free of chloride ions (Tris-HAc). EDX results showed that chloride ions present in Tris-HCl buffer solution were incorporated into the apatite formed during immersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Kirste et al also compared two different Tris formulations, comparing ion release and apatite formation of 45S5 immersed in 0.062 mol L −1 Tris‐HCl and Tris‐HAc, where the pH was adjusted using acetic acid rather than hydrochloric acid. Both solutions had an initial pH of 7.4.…”
Section: Impact Of Immersion Media Compositionmentioning
confidence: 99%
“…Kirste et al also compared two different Tris formulations, comparing ion release and apatite formation of 45S5 immersed in 0.062 mol L −1 Tris‐HCl and Tris‐HAc, where the pH was adjusted using acetic acid rather than hydrochloric acid. Both solutions had an initial pH of 7.4.…”
Section: Impact Of Immersion Media Compositionmentioning
confidence: 99%
“…5 show the FTIR spectra of 0B and 5B after SBF immersion with three different solution treatments (still, adjusted and refreshed), along with a FTIR spectrum of a commercial HAp powder for reference. The appearance of a split phosphate P–O bending band (∼560 and 600 cm −1 ), P–O stretching band (∼1015 cm −1 ) and a carbonate band (∼870 cm −1 ) indicates the formation of HAp [ 46 ]. For both 0B and 5B samples, refreshing SBF every 24 h promotes the HAp formation on glass surface, while still and adjusted treatments exhibit slower and similar HAp formation.…”
Section: Resultsmentioning
confidence: 99%
“…HCO 3 − concentration in SBF can affect the thickness of calcium phosphate formed [ 34 ], as well as the heterogeneity and the crystal size of the calcium phosphate precipitates [ 57 ]. Additionally, it was found that chloride ions in TRIS-HCl butter solution were incorporated in the apatite formation during immersion tests, affecting the final composition of precipitates [ 46 ]. Future detailed compositional studies of formed HAp are desired for better understanding the apatite formation mechanism, which can benefit the improvement of in vitro bioactivity evaluation of glass materials, as well as designing new functional biomaterials (e.g., apatite formed matches bone or dentin tissue [ 58 , 59 ]).…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Indeed, SBF has much more ions dissolved, thus being more saturated and prone to precipitation reactions. Instead, bioactivity behavior was favored in rare earth-containing glasses.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of such different behavior between SBF and TRIS-HCl solution have been attributed to solution ionic strength and supersaturation. [45][46][47] Indeed, SBF has much more ions dissolved, thus being more saturated and prone to precipitation reactions. 28 Besides, silicon concentration in SBF is at least ten times lower than in TRIS-HCl solution, indicating that the ionic strength of SBF solution has slowed glass dissolution, and the effect of rare earth on glass dissolution is not pronounced.…”
Section: Discussionmentioning
confidence: 99%